An Unusual Case of Leg Pain in a Competitive Cyclist: A Case Report and Review of the Literature. (November 2014) - Lindner, Dror; Agar, Gabriel; Domb, Benjamin Gilbert; Beer, Yiftah; Shub, Idit; Mann, Gideon
Cycling has become a popular recreational and competitive sport. The number of people participating in the sport is gradually increasing. Despite being a noncontact, low-impact sport, as many as 85% of athletes engaged in the sport will suffer from an overuse injury, with the lower limbs comprising the majority of these injuries. Up to 20% of all lower extremity overuse injuries in competitive cyclists are of a vascular source. A 39-year-old competitive cyclist had a 5-year history of thigh pain during cycling, preventing him from competing. The patient was eventually diagnosed with external iliac artery endofibrosis. After conservative treatment failed, the patient underwent corrective vascular surgery with complete resolution of his symptoms and return to competitive cycling by 1 year. Since its first description in 1985, there have been more than 60 articles addressing external iliac artery endofibrosis pathology.